Peningkatan Kompetensi Guru Sekolah Dasar Melalui Workshop Asesmen Kompetensi Di Kabupaten Bekasi - Yahya, Adibah; Maryadi, Adi; Yuningsih, Nining; Carwinda, Carwinda; Saepulloh, Asep (Literasi Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
The Elementary School Level (SD) Competency Assessment Workshop is one of the programs of the Bekasi Regency Education Office in 2021. The Bekasi Regency Elementary Level AK Workshop in 2021 is a Continuous Professional Development activity in improving teacher competence, especially for fifth grade elementary school teachers. both in private schools and public schools related to national assessment policies, literacy and numeracy learning in elementary schools, the role of teachers and facilitation of effective learning environments for literacy and numeracy learning in elementary schools, diagnostic assessments, literacy and numeracy questions, and the introduction of digital national assessment platforms. The condition of the Covid-19 pandemic did not dampen the enthusiasm of teachers in participating in workshop activities, this activity was attended by elementary school teachers in the Bekasi Regency area, which was held using the zoom platform. The results of the activity showed that participants understood the material better than before, this was evidenced by the results of the pretest and posttest